Transcriptional Profiling in Experimental Visceral Leishmaniasis Reveals a Broad Splenic Inflammatory Environment that Conditions Macrophages toward a Disease-Promoting Phenotype. - Fanping Kong; Omar A Saldarriaga; Heidi Spratt; E Yaneth Osorio; Bruno L Travi; Bruce A Luxon; Peter C Melby (PLoS Pathogens)
Visceral Leishmaniasis (VL), caused by the intracellular protozoan Leishmania donovani, is characterized by relentlessly increasing visceral parasite replication, cachexia, massive splenomegaly, pancytopenia and ultimately death. Progressive disease is considered to be due to impaired effector T cell function and/or failure of macrophages to be activated to kill the intracellular parasite. In previous studies, we used the Syrian hamster (Mesocricetus auratus) as a model because it mimics the progressive nature of active human VL. We demonstrated previously that mixed expression of macrophage-activating (IFN-γ) and regulatory (IL-4, IL-10, IL-21) cytokines, parasite-induced expression of macrophage arginase 1 (Arg1), and decreased production of nitric oxide are key immunopathologic factors. Here we examined global changes in gene expression to define the splenic environment and phenotype of splenic macrophages during progressive VL. We used RNA sequencing coupled with de novo transcriptome assembly, because the Syrian hamster does not have a fully sequenced and annotated reference genome. Differentially expressed transcripts identified a highly inflammatory spleen environment with abundant expression of type I and type II interferon response genes. However, high IFN-γ expression was ineffective in directing exclusive M1 macrophage polarization, suppressing M2-associated gene expression, and restraining parasite replication and disease. While many IFN-inducible transcripts were upregulated in the infected spleen, fewer were induced in splenic macrophages in VL. Paradoxically, IFN-γ enhanced parasite growth and induced the counter-regulatory molecules Arg1, Ido1 and Irg1 in splenic macrophages. This was mediated, at least in part, through IFN-γ-induced activation of STAT3 and expression of IL-10, which suggests that splenic macrophages in VL are conditioned to respond to macrophage activation signals with a counter-regulatory response that is ineffective and even disease-promoting. Accordingly, inhibition of STAT3 activation led to a reduced parasite load in infected macrophages. Thus, the STAT3 pathway offers a rational target for adjunctive host-directed therapy to interrupt the pathogenesis of VL.